2020
DOI: 10.21203/rs.3.rs-136354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GCKR Common Functional Polymorphisms are Associated with Metabolic Syndrome and its Components: A 10-Year Retrospective Cohort Study in Iranian Adults

Abstract: Background: Some previous studies reported that common functional variants (rs780093, rs780094, and rs1260326) in the glucokinase regulator gene (GCKR) were associated with metabolic syndrome despite the simultaneous association with the favorable and unfavorable metabolic syndrome components. We decided to examine these findings, to our knowledge for the first time, in Iranian adults. We investigated the association of the GCKR variants with incident MetS in mean follow-up times for nearly ten years.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The ndings indicated the association between functional GCKR variants and higher TG and lower fasting blood sugar (FBS) levels. Moreover, the results of Cox-adjusted model regression revealed that TT carriers of rs780094, rs780093, and rs1260326 were associated with a 20, 23, and 21% higher risk of MetS incidence, respectively [41]. The following study reported that the logistic regression model showed a signi cant association of MetS with age, gender, schooling years, BMI, physical activity, rs780094, and rs780093.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The ndings indicated the association between functional GCKR variants and higher TG and lower fasting blood sugar (FBS) levels. Moreover, the results of Cox-adjusted model regression revealed that TT carriers of rs780094, rs780093, and rs1260326 were associated with a 20, 23, and 21% higher risk of MetS incidence, respectively [41]. The following study reported that the logistic regression model showed a signi cant association of MetS with age, gender, schooling years, BMI, physical activity, rs780094, and rs780093.…”
Section: Resultsmentioning
confidence: 71%
“…To investigate the association of MetS and its components with glucokinase regulator (GCKR) polymorphisms (rs780093, rs780094, and rs1260326), linear and logistic regression analyses were used in an additive genetic model. Moreover, Cox regression analysis was carried out to show the variants' association with the incidence of MetS [41]. In a candidate gene study, to nd the optimal prediction model (s) for MetS, GCKR gene variants, along with clinical and demographic information, were used on 4756 eligible TCGS participants.…”
Section: Key Methods and Data Collectionmentioning
confidence: 99%
“…Mammalian Gckr is composed of two sugar isomerase (SIS) domains which contain binding sites for fructose-6-phosphate (F6P) or fructose-1-phosphate (F1P) and glucokinase, where the fructose metabolites alter the affinity of Gckr for glucokinase [79]. Human GCKR has been reported as a diabetic susceptibility gene by several studies [80][81][82][83][84]. We found a full-length second copy of Gckr, LOC117716845, 1.2 Mb downstream of the canonical Gckr.…”
Section: Duplicated Nile Rat Genes That Exist As Single Copy Genes In...mentioning
confidence: 87%
“…(Diabetes Genetics Initiative of Broad Institute of Harvard and MIT, Lund University, and Novartis Institutes of BioMedical Research et al 2007)(Zahedi et al 2021) …”
mentioning
confidence: 99%